The Design of a Mini Plant Factory with Artificial Lighting and Application of Environmental Conditions Control System - Ali Çaylı; Emir Hüseyin Kaya (Turkish Journal of Agriculture: Food Science and Technology)
Due to rapidly increasing population and urbanization, agricultural lands are shrinking. However, environmental problems and pollution are constantly increasing. This poses a threat to agricultural production and food access. In order to overcome these threats, the use of fully controlled indoor production systems called plant factory is becoming widespread. The management of plant nutrition and monitor of environmental conditions is very important for production in the plant factory. Plant production is sensitive to environmental conditions. For this reason, it is necessary to make accurate measurements in order to ensure the correct climatic conditions. The high cost of control systems designed for this purpose is a problem for producers. In this study, a mini plant factory prototype and control system are presented which is developed by using open source hardware and software. In addition, the temperature, relative humidity and light measured by the low-cost sensors were compared with the reference devices and the system performance and stability were investigated.